Clinical Evaluation of a Novel Technology for Oral Patient-Controlled Analgesia, the PCoA® Acute Device, for Hospitalized Patients with Postoperative Pain, in Pilot Feasibility Study - Stefan Wirz; Stefan Conrad; Ronit Shtrichman; Kai Schimo; Eva Hoffmann (Pain Research and Management)
Background. Acute postoperative pain delays recovery and increases morbidity and mortality. Traditional administration of postoperative analgesics by nurses is often inefficient. The present study evaluated the safety, efficacy, and usability of a novel, patient-controlled analgesic dispenser, the PCoA Acute. Methods. A controlled pilot study was conducted at three medical centers. Patients scheduled for elective surgery were enrolled into two groups, both taking oral analgesics: a control group (n=43), opioids dispensed by nurses, and a test group (n=27), opioids dispensed via the PCoA Acute. Pill intake data were recorded. Pain ratings at rest and during movement were surveyed. Results. No severe adverse events were recorded. Average pill intake time was reduced from 8 : 58 minutes in the control group to 1 : 17 minutes in the test group (P value < 0.05). The test group took 67% more pills than the control group, indicating enhanced compliance. Pain scores were significantly lower for patients in the test group (P value < 0.05). Over 90% of PCoA Acute users were satisfied with its use. Conclusions. The study confirmed that PCoA Acute is safe and effective. It is well accepted by patients and medical staff. Its use can optimize pain medication administration.